The role of the gut microbiota in the pathogenesis and therapy of type 2 diabetes mellitus - Madej, Aleksandra; Senat, Hanna; Grabowska, Patrycja; Bolla, Patrycja; Senat, Aleksandra; Marczyńska, Zuzanna; Niemczyk, Anna; Dorochowicz, Mateusz (Journal of Education, Health and Sport, 2024)
INTRODUCTION: Diabetes mellitus type II (DM2) is one of the most frequently diagnosed diseases worldwide with a constantly increasing prevalence. It represents an important clinical challenge. The studies are concentrating on improving our knowledge of both pathogenesis and therapeutic opportunities. The influence of intestinal flora on many health conditions is being investigated. It was found that the gut microbiota of the healthy and diabetic individuals are different. This provides a highly important focus for the consideration of whether and how, based on the content of the intestinal flora, the development and treatment of this disease and its complications can be affected. PURPOSE: The aim of the study is to present the current state of knowledge about the The role of the gut microbiota in the pathogenesis and therapy of type 2 diabetes. MATERIALS AND METHOD: The available literature in PubMed was reviewed to write the article, using the keywords , gut microbiota diabetes”, , diabetes mellitus”, , intestinal microbiome diabetes”, , dysbiosis diabetes” and , gut microbiota diabetes”. CONCLUSION: The intestinal microbiome is a diverse community of microorganisms that inhabit the gut and has been shown to be essential for the health of the body. Modifications in the diversity and frequency of microorganisms residing in the gut, and the accumulation of metabolites they generate, have been correlated with DM2. The study of intestinal microflora could lead to the discovery of new methods of diagnosis and therapies of DM2 and its complications, such as diabetic kidney disease, neuropathy, retinopathy and cardiovascular disease. In conclusion, further studies are needed to understand the role of the gut microbiome in the pathogenesis and therapy of DM2.